Low Profile LTCC Balanced Filter Based on a Lumped Elements Balun for WiMAX Applications - Sakhnenko, Sergiy; Orlenko, Denys; Markov, Konstyantyn; Yatsenko, Andriy; Vorotnikov, Borys; Sevskiy, Georgiy; Heide, Patric; Vossiek, Martin (IEEE International Microwave Symposium 2008, 2008)
This paper reports on a design of a balanced filter based on a new lumped LC type balun. The realization disadvantages of conventional LC baluns integrated In a front-end module have been discussed and a new low profile lumped-element balun has been proposed. The balanced filter is realized as a combination of a second order band pass filter and the novel LC balun with an additional low-pass circuit. The proposed layout has been realized using multilayer low temperature co-fired ceramic (LTCC) technology. The resulting structure exhibits excellent electrical performance, immunity to manufacturing tolerances and compactness. The realized low profile balanced Alter is placed between two ground planes ensuring high electromagnetic compatibility which allows using this balanced filter as a building block of highly integrated WiMAX front-end modules. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.lowpro
Keywords: Balanced filter; Balun; Front-end module; LTCC; WiMAX